2023
DOI: 10.1021/jacs.2c12586
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Neighbored Single-Cobalt Sites Enable Heterogeneous Oxidase-Type Catalysis

Abstract: The development of biomimetic catalytic systems that can imitate or even surpass natural enzymes remains an ongoing challenge, especially for bioinspired syntheses that can access non-natural reactions. Here, we show how an all-inorganic biomimetic system bearing robust nitrogen-neighbored singlecobalt site/pyridinic-N site (Co−N 4 /Py-N) pairs can act cooperatively as an oxidase mimic, which renders an engaged coupling of oxygen (O 2 ) reduction with synthetically beneficial chemical transformations. By devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…This indicates that the anchoring of single-atom Co on ZIS facilitates the adsorption, activation, and further reduction of O 2 , and this is consistent with the stronger signals of ROS on Co 1 /ZIS over the pristine ZIS sample in ESR tests (Figure a,b). To further identify whether the single-atom Co on ZIS functions as the active site for photocatalytic selective aerobic oxidation of HMF, the spiking experiment was performed by adding KSCN to deactivate Co sites. As displayed in Figure f, shielding the Co sites significantly decreased the conversion of HMF (one-third of the original value) and the yield of DFF (one-fourth of the original value), verifying the critical role of the Co single atoms on ZIS as active sites in dramatically improving photocatalytic aerobic oxidation of HMF.…”
Section: Resultsmentioning
confidence: 82%
“…This indicates that the anchoring of single-atom Co on ZIS facilitates the adsorption, activation, and further reduction of O 2 , and this is consistent with the stronger signals of ROS on Co 1 /ZIS over the pristine ZIS sample in ESR tests (Figure a,b). To further identify whether the single-atom Co on ZIS functions as the active site for photocatalytic selective aerobic oxidation of HMF, the spiking experiment was performed by adding KSCN to deactivate Co sites. As displayed in Figure f, shielding the Co sites significantly decreased the conversion of HMF (one-third of the original value) and the yield of DFF (one-fourth of the original value), verifying the critical role of the Co single atoms on ZIS as active sites in dramatically improving photocatalytic aerobic oxidation of HMF.…”
Section: Resultsmentioning
confidence: 82%
“…To further verify the relationship between Co–N 4 sites and catalytic activity, spiking experiments were conducted. SCN – could poison and inactivate metal–N structures. , As shown in Figure S16, the rate constant was reduced by 3.8 times after SCN – treatment, which indicated that Co–N 4 was the main active site. Therefore, Co–N/C-3 with the highest catalytic activity was selected for further study.…”
Section: Resultsmentioning
confidence: 94%
“…In recent times, single-atom catalysts (SACs) have emerged as attractive heterogeneous catalysts owing to their maximum active metal-utilization efficiency. These materials have been excellently utilized for various kinds of catalytic reactions, especially electrocatalysis. Transition metals (Fe, Co, Ni), usually atomically stabilized by N-doped carbons, are the most widely studied SACs. They have been well established due to their high ORR activities. , However, geometric configurations of SACs and electron density at the active metal centers are the most important factors deciding the catalytic performance. In other words, the O 2 adsorption type, the O–O bond length, and the mechanistic pathway are highly involved in determining the ORR activity. Compared to SACs, dual single-atom catalysts (DSACs) can not only tune the electronic structure of active metal sites but also provide a different path for the adsorption and activation of O 2 . Reports suggest that O 2 preferentially interacts with SACs through either end-on or side-on models, while DSACs allow the formation of an – O–O– bridging model.…”
Section: Introductionmentioning
confidence: 99%